ANALISIS POLA DISTRIBUSI SPASIAL DAN AKSESIBILITAS WILAYAH ADMINISTRATIF MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) di kota tegal - Rima Febryani; Bambang Agus Herlambang; Ahmad Khoirul Anam (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to analyze the spatial distribution patterns of the population and the accessibility levels of administrative areas in Tegal City using a Geographic Information System (GIS). The method used is descriptive quantitative with secondary spasial and non-spatial data obtained from related agencies. Data were analyzed using QGIS software to produce maps of population spatial distribution and road network-based accessibility. The results show an uneven population distribution, with the highest concentration in Tegal Timur and Tegal Barat Districts. Accessibility analysis identified areas with high connectivity such as Slawi as regional centers, while areas such as Bumijawa and Bojong have lower accessibility. The use of GIS proves effective in presenting spatial information that can serve as a basis for spatial planning and infrastructure development in Tegal City.